2018
DOI: 10.1038/s41598-018-33636-z
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral resistance, genotypic characterization and origin of Human Immunodeficiency Virus among the infected wives of Intravenous drug users in Manipur

Abstract: Increasing incidence of drug resistance is ascertained to be the main obstacles in limiting the virus among the human immunodeficiency virus (HIV) infected individuals. This study investigates the drug resistance mutations (DRMs), genetic variants and origin of transmitted drug resistance of HIV-1 among the HIV-1 infected wives of intravenous drug users (IDUs) in Manipur. 44 HIV pol gene sequences were generated from 56 blood samples by viral gene amplification and sequencing. Sequences were then analysed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Myanmar shares border with India, China, Bangladesh, Laos and Thailand. Similar SDRM profiles were also observed among ART-naïve HIV-1 individuals in Thailand, 42 India, 43 and China, 11,37 suggesting a possibility of cross-border transmission of HIV-1 drug resistance. This hypothesis was supported by a previous observation that TDRs circulating in the wives of IDUs in Manipur, India, were introduced from Myanmar, Vietnam and/or mainland India.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Myanmar shares border with India, China, Bangladesh, Laos and Thailand. Similar SDRM profiles were also observed among ART-naïve HIV-1 individuals in Thailand, 42 India, 43 and China, 11,37 suggesting a possibility of cross-border transmission of HIV-1 drug resistance. This hypothesis was supported by a previous observation that TDRs circulating in the wives of IDUs in Manipur, India, were introduced from Myanmar, Vietnam and/or mainland India.…”
Section: Discussionsupporting
confidence: 67%
“…This hypothesis was supported by a previous observation that TDRs circulating in the wives of IDUs in Manipur, India, were introduced from Myanmar, Vietnam and/or mainland India. 43 Our previous studies reported a bidirectional crossborder transmission of HIV-1 between Myanmar and China and demonstrated that Burmese LDTDs and Burmese IDUs staying in Yunnan played a crucial role in this cross-border transmission. 29,30,44 In this study, we identified some transmission clusters formed by HIV-1 drugresistant strains in the China-Myanmar border region.…”
Section: Discussionmentioning
confidence: 95%
“…These drugs impair individuals’ judgment, which can lead to risky sexual behavior, such as sex trading for drugs and needle sharing. 11 , 12 , 13 , 14 These impairments under the influence of illegal drugs are also a potent cofactor that impedes timely diagnosis of HIV transmission, pathogenesis, and adherence to therapy. 13 , 15 Clinical studies implicate drug abuse in increased viral load, accelerated disease progression, and worsening of AIDS-related mortality even in ART-adherent patients.…”
Section: Introductionmentioning
confidence: 99%